Hypercholesterolemia Differences based on Body Fat Percentage in Diabetic Patients at Pasar Minggu Primary Health Care 2018 - Asti Shafira; Ratu Ayu Dewi Sartika; Diah Mulyawati Utari (Faculty of Public Health Universitas Indonesia, 2020)
AbstractHypercholesterolemia is the leading predictor of various cardiovascular disease (CVD) which is the leading cause of death in the world. This study aims to determine whether there are a ny differences the incidence of hypercholesterolemia based on factors related to it in people with diabetes mellitus at Pasar Minggu Primary Health Care in 2018. This study used a cross -sectional method with a sample size of 126 respondents using consecutive sampling. Research variables studied were incidence of hypercholesterolemia, sex, duration of diabetes mellitus, family history of diabetes mellitus, smoking habit, physical activity, stress level, body fat percentage and fat intake. The results of this study showed that the prevalence of hypercholesterolemia incidence in DM patients was 56.3% with 37.1% in men and 63.7% in women. Of all independent variables studied, significant differences with statistical analysis were in sex (OR = 2.947, p = 0.009), family history (OR = 0.443, p = 0.018) and smoking habits (OR = 1,233; p = 0.038). Meanwhile, there was no significant the incidence of hypercholesterolemia differences based on duration of diabetes mellitus, physical activity, stress level, body, fat bod y percentage a nd fat intake due to p > 0.05. To conclude, there were significant differences in sex, family history of diabetes mellitus and smoking habits with hypercholesterolaemia incidence, with an increased risk of hypercholesterolemia in line with female sex, family history of DM and active smoking habits.AbstrakHiperkolesterolemia merupakan salah satu prediktor kuat berbagai penyait jantung yang merupakan penyebab utama kema tian di dunia. Penelitian ini bertujuan untuk mengetahui apakah ada perbedaan berbagai faktor yang berkaitan dengan kejadian hiperkolesterolemia pada penderita diabetes melitus di Puskesmas Pasar Minggu pada tahun 2018. Penelitian ini menggunakan metode cr oss-sectional dengan jumlah sampel sebesar 126 responden menggunakan consecutive sampling. Variabel penelitian yang diteliti adalah kejadian hiperkolesterolemia, jenis kelamin, lama menderita diabetes melitus, riwayat DM keluarga, kebiasaan merokok, aktivitas fisik, tingkat stress, persen lemak tubuh dan asupan lemak. Hasil dari penelitian ini menunjukkan bahwa prevalensi kejadian hiperkolesterolemia pada penderita DM adalah 56,3% dengan 37,1% pada pria dan 63,7% pada wanita. Dari seluruh variabel independe nt yang diteliti, perbedaan yang bermakna dengan hasil uji chi square adalah jenis kelamin (OR = 2,947; CI = 1,326 -6,672), riwayat keluarga (OR = 0,443; CI = 0,209 -0,895) dan kebiasaan merokok (OR = 1,233; CI = 0,990 -11,898). Sementara itu, tidak terdapat perbedaan bermakna kejadian hiperkolesterolemia berdasarkan lama menderita DM, aktivitas fisik, tingkat stress, persen lemak tubuh d an asupan lemak karena p > 0,05 . Disimpulkan, terdapat perbedaan yang signifikan pada jenis kelamin, riwayat DM keluarga da n kebiasaan merokok dengan kejadian hiperkolesterolemia . Peningkatan risiko hiperkolesterolemia utamanya terjadi pada perempuan, adanya riwayat DM keluarga dan kebiasaan aktif merokok.